Working from home: negotiations of domestic functionality and aesthetics. Issue 1 (2nd January 2023) - Goodwin, Brittany; Webber, Nicholas; Baker, Tom; Bartos, Ann E.
Abstract: While 'the home' is omnipresent within studies of home-located work, the physical or material qualities of the home tend to be positioned as a stable setting within which occupants manage the social complications of home-work. By contrast, we discuss how domestic materialities play a dynamic role in home-work, and how these materialities are mediated by specificities of tenure, household type, dwelling size and other factors. Bringing literature on home-located work into conversation with studies of domestic materialities, the paper draws on interviews and focus groups involving 11 female entrepreneurs working from their homes in Aotearoa New Zealand. Through discussion of participants' negotiations with the functionality and aesthetics of their homes, the paper shows how domestic materialities actively shape, in enabling and restricting ways, the practice and experience of home-located work, while keeping sight of how such materialities are patterned by household characteristics and housing market conditions. The paper offers topical insights as people and employers grapple with the normalisation and relative (un)viability of home-located work post-Covid.